Accessibility to nodes of interest: Dislocation of the industrial districts of Tuscany - de Candia, Gioacchino (The European Journal of Applied Economics, 2016)
The present research starts by a series of experiences gained by the author on the theme of attractiveness/accessibility of territories, in light of the most recent dynamics for the analysis. The equation model used is of gravitational type. Specifically, the impedance function is used in the form of logistics, which has so far provided the best results in the analysis of territories. The research is conducted at the municipal level. The paper aims to analyze the connection between these works and the map of industrial districts, recently produced by ISTAT. The analyzed region, as in other publications, is Tuscany, which provides the details on the municipal map of accessibility in relation to the location of industrial clusters. The metropolitan city of Florence is treated separately. The aim is to provide policy makers with the best socio-economic information for the economic and financial administration of territories.